Is duct tape therapy effective as a single agent for treating nongenital warts?. Issue 9 (September 2017) - Perkins, Allen; Atkinson, Tangela; Davis, Ashley; Gill, Curtis; Graham, Monique
Abstract : EVIDENCE‐BASED ANSWER : Duct tape is no better than nonmedicated dressing or cryotherapy for the treatment of nongenital warts (SOR: A, meta‐analysis of RCTs).